STUDY ON THE UTILIZATION OF NUSANTARA FISHERY PORT (PPN) KEJAWANAN CIREBON - Fitriani, Devi; Pratiwy, Fittrie M.; Suryana, Asep A. H.; Maulina, Ine (Universitas Mataram, 2025)
The Nusantara Fisheries Port (PPN) Kejawanan in Cirebon City is an important infrastructure that supports the fisheries sector in the northern coastal region of West Java. As a distribution center for fish catches and a driver of the capture fisheries economy, this port is regulated by various regulations, including Law Number 45 of 2009 and Regulation of the Minister of Marine Affairs and Fisheries Number 8 of 2012, which requires the existence of basic, functional, and supporting facilities. This study aims to evaluate the level of facility utilization in PPN Kejawanan using a descriptive method by collecting primary data through observation and interviews, as well as secondary data from port managers. The results of the study show that the PPN Kejawanan has fulfilled 19 of the 22 required facilities, or around 86%, with most of the facilities functioning optimally. However, there are several facilities that are not yet available, such as jetty piers and fishermen's guesthouses. These results indicate the need to increase the utilization of facilities to ensure better port services and support the economic growth of the fisheries sector in PPN Kejawanan.